Development and validation of the interpersonal communication assessment tool for assessing the interpersonal communication skills of public health midwives - S.A.S. Prasanna; H.T.C.S. Abeysena; M.A.A.P. Alagiyawanna (BMC, 2023)
Abstract Background Interpersonal Communication Skills (IPCS) are one of the core clinical skills that should be developed by the Public Health Midwives (PHMs), who are grass-root level public healthcare providers in primary healthcare settings in Sri Lanka. This study aimed to develop and validate the Interpersonal Communication Assessment Tool (IPCAT), an observational rating scale, to assess the IPCS of PHMs. Methods Item generation, item reduction, instrument drafting, and development of the tool's rating guide were made by an expert panel. A cross-sectional study was conducted in five randomly selected Medical Officer of Health (MOH) areas, the smallest public health administrative division in the district of Colombo, Sri Lanka, to identify the factor structure, which is the correlational relationship between a number of variables in the tool. A sample of 164 PHMs was recruited. The data on IPCS were collected by video-recording the provider-client interaction using simulated clients. All recorded videos were rated by a rater using the drafted IPCAT, which included a Likert scale of 1(poor) to 5 (excellent). Exploratory factor analysis was conducted using the Principal Axis Factoring extraction method and the Varimax rotation technique to explore the factors. Three independent raters were used to rate ten randomly selected videos to assess the tool's internal consistency and inter-rater reliability. Results The IPCAT obtained a five-factor model with 22 items, and all five factors explained 65% of the total variance. The resulting factors were "Engaging" (six items on making rapport), "Delivering" (four items on paying respect), "Questioning" (four items on asking questions), "Responding" (four items on empathy), and "Ending" (four items to assess the skills of ending a conversation productively). The internal consistency, Cronbach's Alpha value, for all five factors was above 0.8, and the inter-rater reliability (ICC) was excellent (0.95). Conclusions The Interpersonal Communication Assessment Tool is a valid and reliable tool for assessing the interpersonal communication skills of Public Health Midwives. Trial registration Clinical Trial Registry, Sri Lanka. Ref No, SLCTR/2020/006(February 4th,2020)